Cultivating Gratitude: Essential Korean Thankfulness Phrases for Indonesian Learners - Kwon Youngsun; Somadi Sosrohadi; Citra Andini; Shua Jung; Ko Yookyung; Park Kyeong Jae (Hasanuddin University, 2024)
This research explores various ways of expressing gratitude in the Korean language and their effects on Indonesian learners of Korean. Through the analysis of language variations involving expressions of gratitude in Korean, it highlights differences in formality, familiarity, and intensity of gratitude expressed. This research utilized a descriptive qualitative method. The data for this study were obtained from online books and related articles. The results indicate that understanding various expressions of gratitude has a positive impact on communication skills, politeness, cultural adaptation, and social integration for Indonesian learners. By expanding their knowledge of the Korean language and culture, learners can more easily interact with native speakers, strengthen interpersonal relationships, and gain a deeper understanding of Korean culture as a whole. The implications of this research provide insights into the importance of understanding language variations in social and cultural contexts, as well as their implications for language learning and cross-cultural integration.